Analisis Ketercapaian Standar Isi Pada Sekolah Dasar (SD.S Plus Syania Kec. Cimanggung Kab. Sumedang Jawa Barat) - Ani Jailani; Chaerul Rochman (JIP Jurnal Ilmiah PGMI, 2019)
In Government Regulation No. 19 of 2005 concerning National Education Standards the government formulates Standard standards in the formulation of National Education Standards to improve the quality of education as well as efforts to achieve national education goals in accordance with content standards, process standards, competition standards, educator standards and education staff , standards for facilities and infrastructure, management standards, funding standards, and education calculation standards. For this reason, every formal education institution must implement these standards in the implementation of education. Like challenging at SD Plus Syania Elementary School which is the object of research, where this research aims to examine the application of the Content Standards implemented at the school. From the data obtained, the Implementation of Standard Content in the School meets national standards, made on this standard can be good and supports the better learning process. That can be seen from the conclusion of the observation as; The scoring profile on the Standard Content indicator gets results as much as 90% with the following details: 1) Indicators that get A assessment as much as 80% by agreeing to a score of 80, 2) indicators that get B Value of 5% with scor conditions 10 and 3) indicators get E assessment of 5% by agreeing to score 5. From the data obtained by indicators that have not reached the maximum and lowest scores on indicator 6, where schools have not been able to support integrated thematic based learning and most still use the KTSP Curriculum.